Ethnic Networks and International Trade - Gil S. Epstein; Ira N. Gang (Institute for the Study of Labor (IZA), 2004)
There is a well-established high quality literature on the role of networks, particularly ethnic networks, in international trade. Ethnic networks are a way of overcoming informal barriers (information costs, risk and uncertainty) to trade by building trust and substituting for the difficulty of enforcing contracts internationally. The networks we are interested in are those that form between migrants and natives in the host country and between migrants and their home country. Ethnic networks exist when assimilation is not complete. We consider the struggle of migrants to assimilate and, at the same time, the struggle of the local population to prevent such assimilation. These activities affect trade possibilities. Moreover, we show that it may well be in the interest of migrants who specialize in trade to, at some point in time, turn from investing in assimilation activities and instead invest in anti-assimilation activities in order to preserve immigrants? preferences for home country goods.
Keywords: I20; J61; F23; D74; L14; 330; assimilation; discrimination; contracts; ethnicity; international trade; market structure; network; migration; transnational; Business Network; Ethnische Gruppe; Aussenwirtschaft; Migranten; Internationale Arbeitsmobilität